Analysis of Beer's Criteria 2019 and Patient Characteristics of Potentially Inappropriate Medication in Elderly Patients with Diabetes Mellitus - Dhafin, Anis Akhwan; Putri, Elsa Mahardika (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Background: Elderly patients with type 2 diabetes mellitus with polypharmacy and various comorbidities often have problems with Potentially Inappropriate Medications (PIMs). One of the methods commonly used to detect this event is Beer's Criteria 2019.Objectives: This study aims to: (1) identify the characteristics of elderly hospitalized patients with type 2 DM; (2) analyze the incidence of PIM in patients; and (3) analyze the relationship between characteristics (age, gender, comorbidities, length of stay, and number of drugs given) with the incidence of PIMs.Methods: The research was conducted at two type C hospitals in the city of Bengkulu, with a total of 105 patients using the purposive sampling method. This research is a cross-sectional study with data collection techniques in the form of medical record data from patients for the period January – December 2022 who received drug therapy. Data analysis consists of comparing data with Beer'’s Criteria, quantitative descriptive and Fisher'’s test.Results: The research results showed that: (1) the largest age group in Hospitals ) had comorbidities, the highest number of drugs given was more than 10 types of drugs, and the majority of patients were hospitalized for less than five days; (2) There was an incidence of PIMs of 98.65% (73 patients) in Hospital (3) Statistical tests show that there is no relationship between age, gender, comorbidities, number of medications and length of stay with the incidence of PIMs.Conclusion: There is still inappropriate use of drugs given to elderly DM patients. It is hoped that further researchers will be able to find out the reasons for giving these drugs to elderly patients.